Efficient Rejoining of DNA Double-Strand Breaks despite Increased Cell-Killing Effectiveness following Spread-Out Bragg Peak Carbon-Ion Irradiation - Averbeck, Nicole B.; Topsch, Jana; Scholz, Michael; Kraft-Weyrather, Wilma; Durante, Marco; Taucher-Scholz, Gisela (Frontiers in Oncology, 2016)
Radiotherapy of solid tumors with charged particles holds several advantages in comparison to photon therapy; among them conformal dose distribution in the tumor, improved sparing of tumor-surrounding healthy tissue, and an increased relative biological effectiveness (RBE) in the tumor target-volume in the case of ions heavier than protons. A crucial factor of the biological effects is DNA damage, of which DNA double strand breaks (DSBs) are the most deleterious. The reparability of these lesions determines the cell survival after irradiation and thus the RBE. Interestingly, using phosphorylated H2AX as a DSB marker, our data in human fibroblasts revealed that after therapy-relevant spread-out Bragg Peak irradiation with carbon ions DSBs are very efficiently rejoined, despite an increased RBE for cell survival. This suggests that misrepair plays an important role in the increased RBE of heavy-ion radiation. Possible sources of erroneous repair will be discussed.